Sea ice diatom contributions to Holocene nutrient utilization in East Antarctica - Panizzo, Virginia; Crespin, Julien; Crosta, Xavier; Shemesh, Aldo; Masse, Guillaume; Yam, Ruth; Mattielli, Nadine; Cardinal, Damien (American Geophysical Union, 2014)
Combined high-resolution Holocene δ30Sidiat and δ13Cdiat paleorecords are presented from theSeasonal Ice Zone, East Antarctica. Both data sets reﬂect periods of increased nutrient utilization by diatomsduring the Hypsithermal period (circa 7800 to 3500 calendar years (cal years) B.P.), coincident with a higherabundance of open water diatom species (Fragilariopsis kerguelensis), increased biogenic silica productivity(%BSi), and higher regional summer temperatures. The Neoglacial period (after circa 3500 cal years B.P.) isreﬂected by an increase in sea ice indicative species (Fragilariopsis curta and Fragilariopsis cylindrus,upto50%) along with a decrease in %BSi and δ13Cdiat(< 18‰ to 23‰). However, over this period, δ30Sidiatdata show an increasing trend, to some of the highest values in the Holocene record (average of +0.43‰).Competing hypotheses are discussed to account for the decoupling trend in utilization proxies including ironfertilization, species-dependent fractionation effects, and diatom habitats. Based on mass balance calculations,we highlight that diatom species derived from the semi-enclosed sea ice environment may have a confoundingeffect upon δ30Sidowncorecompositions of the seasonal sea ice zone. A diatom composition, with approximately28% of biogenic silica derived from the sea ice environment (diat-SI) can account for the increased averagecompo sition of δ30Sidiatduring the Neoglacial. These data highlight the signiﬁcant role sea ice diatoms can playwith relation to their export in sediment records, which has implications on productivity reconstructions fromthe seasonal ice zone.